ANALISIS TEORITIS DAN EKSPERIMENTAL LENDUTAN BATANG PADA BALOK SEGIEMPAT DENGAN VARIASI TUMPUAN - Mustopa, Mustopa; Naharuddin, Naharuddin (MEKTEK, 2005)
The aim of this researh is to analyze about deflection which is theoretically or experimentally happened to block square by using various foothold. Integration method and of the bending moment diagram method are used in this researh. There are some factors which effect the action of deflection such as kind and big load, given-force, strength of materials, and kind of foothold